Contrast Microsphere Destruction by a Continuous Flow Ventricular Assist Device: An In Vitro Evaluation Using a Mock Circulation Loop. (13th August 2017) - Platts, David G.; Bartnikowski, Nicole; Gregory, Shaun D.; Scalia, Gregory M.; Fraser, John F.
Abstract : Objectives . Transthoracic echocardiography (TTE) is fundamental in managing patients supported with ventricular assist devices (VAD). However imaging can be difficult in these patients. Contrast improves image quality but they are hydrodynamically fragile agents. The aim was to assess contrast concentration following passage through a VAD utilising a mock circulation loop (MCL). Methods . Heartware continuous flow (CF) VAD was incorporated into a MCL. Definity® contrast was infused into the MCL with imaging before and after CF-VAD. 5 mm 2 regions of interest were used to obtain signal intensity (decibels), as a surrogate of contrast concentration. Results . Four pump speeds revealed significant reduction in contrast signal intensity after CF-VAD compared to before CF-VAD (all p < 0.0001 ). Combined pre- and postpump data at all speeds showed a 22.2% absolute reduction in contrast signal intensity across the CF-VAD (14.8 ± 0.8 dB prepump versus 11.6 ± 1.4 dB postpump; p < 0.0001 ). Mean signal intensity reduction at each speed showed an inverse relationship between speed and relative reduction in signal intensity. Conclusion . Contrast microsphere transit through a CF-VAD within a MCL resulted in significant reduction in signal intensity, consistent with destruction within the pump. This was evident at all CF-VAD pump speeds but relative signal drop was inversely proportional to pump speed.